THE SIGNIFICANCE OF THEOREMS IN TEACHING MATHEMATICS - Ummatova Makhbuba Akhmedovna; Muhiddinova Maftunabonu Akhadjan's Daughter (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The goal of this service is to encourage students' interest in mathematics and increase their understanding of concepts by showing how theorems relate to everyday life. The service method involves creating educational materials such as theorems, teacher training workshops, collaborative learning, and action research in schools. Results include the creation of new learning modules, increased student understanding of problem solving, and the discovery of innovative teaching methods. The effects of this service include improving the quality of mathematics education, developing a more relevant curriculum, increasing students' abilities in critical and analytical thinking through theorem-based problem solving, and increasing students' abilities in critical and analytical thinking.